C45 LATE CARDIAC OUTCOMES IN PATIENTS AFTER COVID–19: A CARDIAC MAGNETIC RESONANCE STUDY. (18th May 2022) - Leonardo, F; Figini, F; Pederzoli, L; Geremia, G; Landi, P; Pingitore, A
Abstract: Background: Myocardial injury can occur in patients with coronavirus disease (COVID)–19. Cardiac magnetic resonance (CMR) provides information on functional and morphological cardiac parameters, as well myocardial tissue characterization. Actually, there are few data on late cardiac outcomes in patients after COVID–19. Aim of the Study: To assess late functional, morphological and myocardial tissue parameters in patients positive to COVID–19 Methods 55 patients (age 50±16 yrs, Female n = 17) with a prior diagnosis of COVID 19, without a previous history of cardiac disease were enrolled in the study. Of these, 35 were hospitalized. The time interval between COVID–19 diagnosis and CMR was 418±28 days. Cardiac function and myocardial tissue characterization have been evaluated with the current CMR techniques. In particular, the presence of late gadolinium enhancement (LGE), as a sign of myocarditis outcome has been evaluated. Results: LGE was present in 19 patients (34.5%). In all cases, LGE was localized at the level of lateral wall of left ventricle within the myocardium or at the subepicardial level (non–ischemic pattern). Left and right ventricular (LV, RV) ejection fraction were within normal values (mean±SD 65±5% and 65±7%, respectively), as well as volumes (LV endiastolic and endsystolic volumes 71±15 and 27±8 ml/m2; RV endiastolic and endsystolic volumes 72±15 and 25±9 ml/m2). In one case, LGE was associated to regional wall hypokinesia. Among the hospitalized patients, the following factors were associated to the presence of LGE: prone position during assisted ventilation, duration of hospitalization. LGE was present in 67% of patients put in prone position, against 33% of patients not pronated (p = 0.009 Fisher's exact test). Duration of hospitalization was 9±5 and 16±7 respectively in patients without and with LGE (p = 0.007) Conclusion: LGE, as an outcome of myocarditis, is present in a significant number of patients with a history of COVID–19, but it is not associated with dilatation or global and regional dysfunction of left ventricle. LGE is mainly present in pts with more severe clinical presentation of COVID–19